PERAN PUBLIC RELATIONS TERHADAP MENINGKATKAN CITRA PERUSAHAAN PT. TRAKINDO MANADO - Rondonuwu, Sintje (Sam Ratulangi University, 2016)
ABSTRACt: It is the strategy of public relations that can maintain the corporate image of PT. Trakindo ofManado. This can be scen from the result of the research held in the PT. Trakindo. There are eightresponalent we interview and their answer is the etnology of public relations of PT. Trakindo of Manadomaintain the corporate image of it self and also because it has its vision and mission and then it appliesthe good corporate governance aand code of conduct. Using the six clssification of kenneth boulding, theanalysis of mmine has shown that 36 item have given the coower that PT. Trakindo of Manado cru bemaintainng the corporate image, even its corporate image is strong and mative. In coclusion the sstrategyof public relations of PT.Trakindo of Manado can be maintrining its corporate image, even its corporateimge is strong and nature.Key Words : Public Raltions, maintraining, corporate image